SUMO2/3 participates in regulating the protective effect of propofol on human umbilical vein endothelial cells. Issue 1 (1st January 2019) - Li, Peng; Liu, Libing; Wang, Tianyu; Chen, Huayong
Abstract: The present study investigated the role and mechanism of SUMO2/3 in the protection of vascular endothelial cells by propofol. An ischemia-reperfusion (I/R) injury model of human umbilical vein endothelial cells (HUVECs) was constructed. After treatment with propofol, we determined the expression of SUMO2/3 proteins by Western blotting, cell proliferation by CCK-8 assay, cell migration by Transwell assay and apoptosis by flow cytometry. After interference of SUMO2/3, the biological functions of HUVECs were observed. Using Western blotting and laser scanning confocal microscopy, the autophagy of HUVECs was examined. Using immunoprecipitation, the SUMO modification site of Beclin1 was examined. The results showed that I/R injury decreased the proliferation and migration and promoted the apoptosis of HUVECs, and propofol restored the normal biological functions to HUVECs. I/R injury inhibited the expression of SUMO2/3 in HUVECs, and propofol increased the expression of SUMO2/3 in HUVECs. Interference of SUMO2/3 expression suppressed the proliferation and migration, and promoted the apoptosis of HUVECs. Propofol exerted its protective effect on HUVECs via autophagy mediated by SUMO2/3 proteins. Beclin1 was modified by SUMO2/3 at the K26 site. SUMO modification of the K26 site in Beclin1 was involved in the regulation of autophagy of HUVECs, and K26R Beclin1 had reduced effect in activating autophagy of HUVECs compared with wild-type Beclin1. These results demonstrate that SUMO2/3 participates in regulating the protective effect of propofol on HUVECs. SUMO2/3 activates the autophagy activity of cells by modifying the K26 site of Beclin1, thus inhibiting I/R injury to vascular endothelial cells.